Case report: Intradural-extramedullary cervical spine clear cell meningioma mimicking a schwannoma in a child - Xiang Yang; Chongxi Xu; Seidu A. Richard; Yongliang Jiang; Jiaxi Wang; Bin Xu; Jianguo Xu; Hao Li (Frontiers in Oncology)
Clear cell meningioma (CCM) is an exceedingly rare subtype of meningioma, with spinal occurrences being even more uncommon. It predominantly affects children and is characterized by a high recurrence rate and poor prognosis, posing significant challenges for clinical treatment. Currently, gross total resection (GTR) is the best approach to reduce recurrence and improve prognosis in these patients. However, detailed descriptions of intraoperative findings, particularly for intraspinal cervical CCM, are scarce in the literature. Here, we report a rare case in which the upper cervical spinal CCM mimicked a schwannoma, detailing the surgical treatment strategy and prognosis. Additionally, we analyzed all previously reported cases of spinal CCM to investigate the clinical characteristics, optimal treatment strategies, and prognostic factors, which may be of particular interest to neurosurgeons.